Relationship between Access to Clean Water and Child Growth and Development in Kenya - Onditi, Liam (Global Journal of Health Sciences, 2024)
Purpose: The aim of the study was to analyze the relationship between access to clean water and child growth and development in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Access to clean water significantly impacts child growth and development in Kenya by reducing waterborne diseases like diarrhea, improving hygiene practices, and ensuring adequate hydration. Children with reliable access to clean water experience better nutritional outcomes and enhanced immune function, crucial for their physical growth and cognitive development. Unique Contribution to Theory, Practice and Policy: Ecological systems theory (Bronfenbrenner), health belief model (Rosenstock) & social determinants of health (SDH) theory may be used to anchor future studies on relationship between access to clean water and child growth and development in Kenya. Expand the implementation of effective water purification technologies and community water supply projects in resource-constrained environments. Advocate for integrated policies that prioritize water security alongside nutrition-sensitive interventions. Policies should support multi-sectoral collaboration between health, water, and sanitation sectors to address the complex interplay between water access and child nutrition.